2022
DOI: 10.1177/16878132221136942
|View full text |Cite
|
Sign up to set email alerts
|

A nonlinear total variation based denoising method for electrostatic signal of low signal-to-noise ratio

Abstract: Aero-engine electrostatic monitoring technology (EMT) is a novel and effective condition monitoring technology. With the help of EMT, effective monitoring of early failures can be achieved. Since the electrostatic monitoring of the running engine will be strongly interfered, the sampled electrostatic signal has various noise components and low signal-to-noise ratio (SNR). After analyzing the source of the noise components carried by the electrostatic signal, this paper proposes a method for electrostatic signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Additionally, the method requires manual specification of the number of VMD modes, which can be a limitation. (4) TVD [19] shows a notable improvement in reducing noise while preserving the main features of the signal in Figure 20d. It effectively suppresses noise, resulting in a cleaner signal.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Additionally, the method requires manual specification of the number of VMD modes, which can be a limitation. (4) TVD [19] shows a notable improvement in reducing noise while preserving the main features of the signal in Figure 20d. It effectively suppresses noise, resulting in a cleaner signal.…”
Section: Discussionmentioning
confidence: 95%
“…This duration is sufficient to observe transient behaviors in the system under study without unnecessary data redundancy. We selected a 2000 Hz sampling rate based on best practices from several studies and similar research in signal processing [19,[32][33][34]. According to the Nyquist theorem, these studies recommend a sampling rate of at least twice the highest frequency component in the signal.…”
Section: The Design Of the Simulation Signalmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, However, during the actual engine testing, it was observed that the electrostatic sensor had hysteresis. When high-speed airflow from the engine passes through the sensor, the particle fault signal often appears as a positive pulse signal (for particles carrying a positive charge) or a negative pulse signal (for particles carrying a negative charge) [52], as shown in Figure 13. For the same input quantity, the input signal for the sensor's positive excursion (increasing input quantity) or negative excursion (decreasing input quantity) is not of equal magnitude, and this phenomenon is known as hysteresis.…”
Section: Charge Determinationmentioning
confidence: 99%